Implementasi Pengamanan Terhadap Server Menggunakan Next Generation Firewall (NGFW) - Nuriana, Syahrul Ramadhan; Sutanto, Imam; Anwar, Nizirwan (Ikatan Ahli Informatika Indonesia, 2024)
The high use of information technology carries a significant risk of cyber attacks, making it important for organisations to secure their servers to prevent intrusion and data leaks. This research focuses on the development and implementation of a CheckPoint Next Generation Firewall (NGFW) configured to mitigate cyber attacks, especially those included in the OWASP Top 10, with a Network Development Life Cycle (NDLC) approach. The research results show that implementing NGFW effectively improves server security and protects against cyber attacks. These findings emphasize the importance of NGFWs in an organization's network security architecture, with the right configuration serving as a proactive mitigation tool against cyber threats.